PERAN ECOBRICK SEBAGAI MEDIA TEPAT GUNA DALAM MENGURANGI LIMBAH PLASTIK DI KOTA MAKASSAR - Febrianti, Dera; Zulfadli, Muhammad; Rusdi, Rusdi; Padli, Feri; Falihin, Dalilul (Universitas Negeri Makassar, 2024)
This study aims to:1) Find out the role of Ecobricks as appropriate media in reducing plastic waste. 2) Find out how to process plastic waste into Ecobricks. 3) Find out how the concepts, ideas or ideas applied to the design of educational media for processing plastic waste into ecobricks can be accepted by the wider community. The type of research used is descriptive qualitative research. The data collection techniques are through observation, interviews, and documentation. The data collection process carried out in this study includes: Data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that; 1) by utilizing Ecobrick media, we can reduce scattered plastic waste that can disrupt community activities on land and at sea. Ecobricks can reduce plastic waste and can also be useful in everyday life. For example, by making tables or chairs with Ecobricks. How to make Ecobricks itself. How to process plastic waste into ecobricks is by inserting pieces of plastic that have been cleaned into disposable plastic bottles, then piercing them using wooden sticks until solid. After the bottle is full of solid plastic, the ecobrick can be made into more useful objects. 4) to attract people to be aware of environmental cleanliness and be able to process their own waste, namely by conducting environmental workshops, Ecobrick making training, and conducting comprehensive socialization to the surrounding community.